Spanish ATLAS Tier-2: facing up to LHC Run 2. Issue 5 (December 2015) - González de la Hoz, S; Peso, J Del; Fassi, F; Casani, A Fernández; Kaci, M; Pellicer, V Lacort; Montiel, A Del Rocio; Oliver, E; Pages, A Pacheco; Sánchez, J; Martínez, V Sánchez; Salt, J; et al.
Abstract: The goal of this work is to describe the way of addressing the main challenges of Run 2 by the Spanish ATLAS Tier-2. The considerable increase of energy and luminosity for the upcoming Run 2 with respect to Run 1 has led to a revision of the ATLAS computing model as well as some of the main ATLAS computing tools. In this paper, the adaptation to these changes will be described. The Spanish ATLAS Tier-2 is a R&D project which consists of a distributed infrastructure composed of three sites and its members are involved in ATLAS computing progress, namely the work in different tasks and the development of new tools (e.g. Event Index).